Mobile Robotics and Autonomous Mapping: Technology for a more Sustainable AgricultureThe introduction of robotics and automation, coupled with Geomatics techniques, could provide notable benefits not only in terms of crop production and land use optimizat - Eleonora Maset; Lorenzo Scalera; Diego Tiozzo (GEOmedia, 2022)
The introduction of robotics and automation, coupled with Geomatics techniques, could provide notable benefits not only in terms of crop production and land use optimization, but also to reduce the use of chemical pesticides, improving sustainability and climate performance through a more results-oriented model, based on the use of updated data and analyses. For these reasons, the implementation of autonomous and robotic solutions together with advanced monitoring techniques is becoming of paramount importance in view of a resilient and sustainable agriculture.